Analysis of The Influence of Economic Stability, Economic Growth and Level of Human Resource Readiness on Income Equality - Sukriyadi, Sukriyadi; Raraga, Filus; Br Ginting, Jenni Veronika; Ladjin, Nurjanna; Haribowo, Rio (International Journal of Engineering, Science and Information Technology, 2024)
This research aims to determine the complex relationship between inequality and income levels, as well as between education and wage inequality. The analysis will employ a random sample from the population, gathered through surveys and observations. With a sample size of 100. Data analysis uses regression. These findings suggest that other factors may also play a role in determining inequality trends and the need for a more contextual approach in formulating effective economic policy. The analysis highlights the complexity of labor market dynamics in the relationship between education and wage inequality. The findings reveal that factor such as the population's educational structure, the quality of education, and unobservable factors, in addition to the level of education itself, influence the effect of education on wages. Overall, the results of the analysis show that education has a very important role in determining income distribution and economic equality. Increased education can reduce wage inequality between individuals with different levels of education, with several contributing factors including improvements in the quality of the workforce, greater opportunities for individuals to obtain qualifications that suit labor market needs, and changes in the way society and the labor market.